Modern Investigation toward Shari’ah Compliance: Squatting Uroflowmetry - Redzuan, Muhd Zaki Azre; Kamarulzaman, Mohd Nazli; Ghazali, Hamid (IIUM Medical Journal Malaysia, 2018)
INTRODUCTION: Standard uroflowmetry is performed in a standing position and it is an important investigation for those who are suspected of having lower urinary tract symptoms such as benign prostatic hyperplasia (BPH). Effects of changing positions during uroflowmetry have also been investigated previously but mixed conclusions were made. For Muslims, voiding in squatting position is encouraged as part as daily practice. This is mainly due to cleanliness reason and many Hadiths have emphasised about it. Objective: The aim of this study is to compare uroflowmetry findings between squatting and standing positions amongst BPH patients attending urology clinic Hospital Tengku Ampuan Afzan (HTAA). Methods: This is a cross section observational study carried out from March 2015 to December 2015. The maximum flow rate, average flow rate, voiding volume, total voiding time and post-voiding residual volume were measured and recorded. Results: The results were then compared and analysed. 64.2% of patients were non-Muslims. 78.0% of the patients voiding habit were standing and 12.2% squatting position at home. The average International Prostate Symptom Score (IPSS) was 12.07 and 63.4% of them were in moderate group disease. Post void residual (PVR) volume showed a reduction in squatting position (p<0.05). Otherwise there was no significant difference seen in other parameters. Conclusion: This study showed that voiding in squatting position, which is shari’ah compliant is not inferior compare to standard uroflowmetry. Therefore Muslim patients should be given the option to perform uroflowmetry in a squatting position if available. This may yield better results.